Inclusive semileptonic B0s meson decays at the LHC via a sum-of-exclusive modes technique: possibilities and prospects - De Cian, Michel; Feliks, N.; Rotondo, M.; Vos, K. Keri (Journal of high energy physics, 2024)
We propose an approach for measuring the moments of the hadronic invariant mass distribution in semileptonic B0s meson decays using a sum-of-exclusive technique. Using the present and foreseen knowledge about exclusive semileptonic B0s decays, we estimate the uncertainties on moments of the kinematic distribution. Semileptonic B0s decays can be described, as their B0 counterpart, using the Heavy Quark Expansion (HQE), with the only difference between the B0s and B0 mesons being the SU(3)F breaking effects that change the numerical values of the non-perturbative HQE parameters. We extract the HQE parameters for the B0s decays from our estimates of the moments, showing the potential of the proposed method. We identify a set of required measurements for a future precision measurement.
Im Text ist "0" hochgestellt, "s" tiefgestellt
Gesehen am 10.01.2025